2010
DOI: 10.1002/tox.20654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublethal hexavalent chromium exposure on the pituitary‐ovarian axis of a teleost, Channa punctatus (Bloch)

Abstract: Exposure to sublethal hexavalent chromium (as 2 and 4 mg L⁻¹ potassium dichromate for 1 and 2 months) during late preparatory to mid prespawning phase of annual reproductive cycle severely affected the pituitary-ovarian axis of a teleost Channa punctatus. Gonadosomatic index (GSI), ovarian histopathology, immunocytochemistry of the pituitary gonadotrophs (LHβ-immunoreactive cells), and serum 17β-estradiol level revealed distinct dose and duration-dependent effects. Gonadosomatic index was declined. Diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The involvement of oxidative stress in heavy metal toxicity is known. CrVI exposure-induced impairment of the pituitary-ovarian axes in Teleost, Channa punctatus (Bloch) was reported (Mishra and Mohanty, 2012). CrVIinduced oxidative stress in mouse (Rao et al, 2009) and rat ovary (Samuel et al, 2012) and uterus (Samuel et al, 2011b) were known.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of oxidative stress in heavy metal toxicity is known. CrVI exposure-induced impairment of the pituitary-ovarian axes in Teleost, Channa punctatus (Bloch) was reported (Mishra and Mohanty, 2012). CrVIinduced oxidative stress in mouse (Rao et al, 2009) and rat ovary (Samuel et al, 2012) and uterus (Samuel et al, 2011b) were known.…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary-thyroid axis is one of the three major endocrine axes of teleosts which play important roles in a number of physiological and metabolic processes (Vijayan and Moon, 1992;Blanton and Specker, 2007;Carr and Patino, 2011). Although hexavalent chromium exposureinduced impact on the pituitary-ovarian (Mishra and Mohanty, 2012a, b) and pituitary-interrenal (Mishra and Mohanty, 2009a, b) axes have been demonstrated, effect on pituitary-thyroid axis has not been well reported. Teles et al (2005) have reported the effect of Cr(VI) exposure in BNF (PAH-like compound)-pretreated European eel, but effective dose level was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…It is easily reduced to Cr(III) and during these transformations, reactive oxygen species (ROS) and reactive nitrogen species (RNS), which have an indisputable role in carcinogenesis, can be formed [21][22][23]. However, chromium is recognized as a metalloestrogen; there are only a few reports in the available literature on chromium/estrogen interaction [24][25][26]. There is no information about the role of estradiol metabolites in exposure to chromium in cancerogenesis.…”
Section: Introductionmentioning
confidence: 99%